Representation of multiculturalism and thriving unity in Kashmir through two regional newspapers: Daily excelsior and Greater Kashmir - Honey Sharma, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2024)
The pious land of Kashmir was created from a sacrosanct river by revered sage Kashyap. The ethereal province of Kashmir withholding its Hindu roots has witnessed the torrential rains of violence proselytization, cooperation, displacement and now invigorating breeze of Chinar leaves with unity and multiculturalism. Regional newspapers hold an important value to disseminate news carrying proximity value. Thus, making it a notable carrier for representation of local people’s precious culture. Regional newspapers create a powerful impact on readers portraying the importance of their identity and thus fostering the cultural discourse among people. The resplendent snowy land of Jammu & Kashmir and its hospitable inhabitants carry rich cultural tapestry that is vast just like its high piqued picturesque vanilla draped mountains. In this study the coverage by two prominent regional newspapers, Daily Excelsior and Greater Kashmir of significant aspects of culture, unity in faith, identical traditional delicacies along with rearrival of Hindu festivals in form of news, articles, editorials and features will be examined.